2018
DOI: 10.1097/tgr.0000000000000176
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sensory Neuromuscular Electrical Stimulation on Swallowing in the Elderly Affected by Stroke

Abstract: Background: Few studies show the effectiveness of neuromuscular electrical stimulation (NMES) in the rehabilitation of neurogenic dysphagia. Objective: To evaluate the effect of sensory NMES on swallowing in elderly patients with stroke sequelae. Methods: Ten poststroke elderly patients were submitted to swallowing video fluoroscopy, from which the degree of oropharyngeal dysphagia was ranked through the Dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…A total of 21 articles were found, of which eleven were focused on experimental researchs [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] and nine were randomized-controlled trials [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. The methodological characteristics of the analysed studies are shown in Table 2 and, in Table 3 , the characteristics of the interventions applied in them are presented.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 21 articles were found, of which eleven were focused on experimental researchs [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] and nine were randomized-controlled trials [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. The methodological characteristics of the analysed studies are shown in Table 2 and, in Table 3 , the characteristics of the interventions applied in them are presented.…”
Section: Resultsmentioning
confidence: 99%
“…The application of NMES was not conducted using the same parameters in the analysed investigations. Regarding the application frequency, the choice of 80 Hz was the most widely used [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 35 , 36 , 37 , 39 , 40 , 41 , 42 , 45 ], although, in several cases, this parameter was not mentioned [ 34 , 38 , 44 , 46 ] and in another two studies the authors selected lower frequencies (60 [ 47 ] and 30 Hz [ 43 ]). In all cases, the results were statistically significant; even those studies which used lower frequencies obtained significant reductions in oral and pharyngeal transit time [ 47 ], significant decreases in the severity of penetration and aspiration [ 43 ] and significant increases in the level of oral intake and quality of life [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations